Fe-Sn-N-C cathode oxygen reduction catalyst as well as preparation method and application thereof
Through chemical vapor deposition of the graphite intercalation of the tin-based precursor and the nitrogen-carbon substrate and the iron-based precursor, the Fe-Sn-N-C catalyst at the single-atom site of the Fe-Sn bimetallic catalyst is formed, solving the stability and resource problems of traditional catalysts in fuel cells, and achieving efficient oxygen reduction catalytic and cycling stability.
Patent Information
- Application Number
- CN202411852116.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-16
AI Technical Summary
Traditional precious metal catalysts have problems such as high cost, insufficient resources and poor stability in proton exchange membrane fuel cells. Non-precious metal single-atom catalysts have severe dissolution of single-atom sites in acidic oxygen reduction environments, resulting in low catalytic efficiency and poor stability.
By mixing heating with a tin-based precursor and a nitrogen-carbon substrate, tin is inserted into the inside of the carbon-nitrogen substrate and the Sn-N4 active site between tin and nitrogen is fixed by calcination. Subsequently, the iron-based precursor and the Sn-N-C composite solid were chemically vapor-deposited, and part of the tin was replaced to form a Fe-Sn bimetallic monoatomic site supported inside the nitrogen-carbon substrate.
The catalytic activity and stability of the Fe-Sn-N-C cathode oxygen reduction catalyst is improved, the dissolution of iron and tin active sites is reduced, the half-wave potential and cyclic stability in the acid oxygen reduction reaction is enhanced, and the voltage output and energy efficiency of the fuel cell are improved.
Smart Images

Figure CN119742380A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts and preparation thereof, and in particular to a Fe-Sn-NC cathode oxygen reduction catalyst and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane fuel cell (PEMFC) is a new type of energy conversion device that is relatively environmentally friendly. However, traditional fuel cells mostly use precious metal catalysts, especially as cathode oxygen reduction catalysts. Precious metal catalysts have disadvantages such as high cost and insufficient resources, which hinder the large-scale application of proton exchange membrane fuel cells.
[0003] Non-precious metal single-atom catalysts have low cost and high catalytic activity. However, in proton exchange membrane fuel cells, the dissolution of non-precious metal sites will cause a significant reduction in the loading of single-atom active centers, making non-precious metal single-atom catalysts exhibit poor stability and low catalytic efficiency in practical applications. Summary of the invention
[0004] In view of this, in order to at least partially solve at least one of the above-mentioned technical problems, the present invention provides a Fe-Sn-NC cathode oxygen reduction catalyst and a preparation method and application thereof.
[0005] According to an embodiment of one aspect of the present invention, a method for preparing a Fe-Sn-NC cathode oxygen reduction catalyst is provided, comprising: pyrolyzing ZIF-8 having a regular dodecahedral framework structure under a protective atmosphere to obtain a carbonized nitrogen-carbon substrate, wherein the nitrogen-carbon substrate has a regular dodecahedral framework structure; mixing and heating a tin-based precursor with the nitrogen-carbon substrate to obtain a tin-intercalated nitrogen-carbon substrate; calcining the tin-intercalated nitrogen-carbon substrate to obtain a Sn-NC composite solid; and chemically vapor depositing the Sn-NC composite solid and an iron-based precursor to obtain a Fe-Sn-NC cathode oxygen reduction catalyst.
[0006] According to an embodiment of the present invention, chemical vapor deposition of a Sn-NC composite solid and an iron-based precursor to obtain a Fe-Sn-NC cathode oxygen reduction catalyst includes: chemical vapor deposition of the Sn-NC composite solid and the iron-based precursor at 700-800°C and under inert gas conditions for 2-4 hours to obtain a Fe-Sn-NC cathode oxygen reduction catalyst precursor; acid washing and drying the Fe-Sn-NC cathode oxygen reduction catalyst precursor to obtain a Fe-Sn-NC cathode oxygen reduction catalyst.
[0007] According to an embodiment of the present invention, mixing and heating a tin-based precursor and a nitrogen-carbon substrate includes: grinding the tin-based precursor and the nitrogen-carbon substrate at room temperature for 10 to 20 minutes to obtain a mixture; heating the mixture from room temperature to 300 to 400°C, maintaining the temperature at 300 to 400°C for 1 to 3 hours, and a heating rate of (4 to 6)°C / min.
[0008] According to an embodiment of the present invention, the molar ratio of the tin-based precursor to the nitrogen-carbon substrate is 1:(1-7.5), and the tin salt precursor includes at least one of tin tetrachloride, tin tetrachloride hydrate, and stannous chloride.
[0009] According to an embodiment of the present invention, calcining a tin-intercalated nitrogen-carbon substrate to obtain a Sn-NC composite solid includes: under a protective atmosphere, heating the tin-intercalated nitrogen-carbon substrate from (300-400)°C to 750°C at a heating rate of (4-6)°C / min, and calcining at 750°C for 1.5-2.5h, then heating to 900°C at a heating rate of (4-6)°C / min, and continuing to calcine at 900°C for 0.5-1.5h to obtain a Sn-NC composite solid.
[0010] According to an embodiment of the present invention, the iron-based precursor includes at least one of ferrous chloride, ferrous chloride hydrate, and ferric chloride; and the molar ratio of the Sn-NC composite solid to the iron-based precursor is (1-1.5):1.
[0011] According to an embodiment of the present invention, the pH of the pickling is 0.5-1.5, and the drying temperature is 60°C.
[0012] According to an embodiment of the present invention, ZIF-8 is prepared by the following process: zinc nitrate or its hydrate and dimethylimidazole are dispersed in a methanol solution and mixed to obtain a mixed solution; the mixed solution is centrifuged and dried in sequence to obtain ZIF-8; the mass ratio of zinc nitrate or its hydrate and dimethylimidazole is (2~4): (5.5~7.5).
[0013] According to an embodiment of another aspect of the present invention, there is provided an Fe-Sn-NC cathode oxygen reduction catalyst prepared by the preparation method as described above, comprising: a nitrogen-carbon substrate having a regular dodecahedral framework structure; and an active center comprising a Fe-Sn bimetallic single atom site supported inside the nitrogen-carbon substrate; wherein iron and tin are coordinated to form a bond, and the mass fraction of iron in the Fe-Sn-NC cathode oxygen reduction catalyst is 1-2%.
[0014] According to another embodiment of the present invention, there is provided an application of the Fe—Sn—NC cathode oxygen reduction catalyst as described above in the field of cathode technology of proton exchange membrane fuel cells.
[0015] According to an embodiment of the present invention, a tin-based precursor is mixed and heated with a nitrogen-carbon substrate, and the graphite intercalation ability of the tin-based precursor is used to insert tin into the interior of the carbon-nitrogen substrate. After calcination, a Sn-N4 active site is formed between tin and nitrogen and fixed to the interior of the carbon-nitrogen substrate. Through the vapor deposition of an iron-based precursor and a Sn-NC composite solid, iron replaces part of the tin in Sn-N4 to form a Fe-Sn bimetallic single atom site loaded on the interior of the nitrogen-carbon substrate, so that the Fe-Sn-NC cathode oxygen reduction catalyst has a higher active site density and stronger stability.
[0016] The excellent graphite intercalation ability of the tin-based precursor allows the tin-based precursor to be evenly distributed between the graphite layers of the nitrogen-carbon substrate, interacting with nitrogen to form new active sites, increasing the number of catalytic sites for oxygen reduction reactions on the nitrogen-carbon substrate, thereby increasing the density of active sites and improving the catalytic activity of the Fe-Sn-NC cathode oxygen reduction catalyst. The intervention of the tin-based precursor modifies the graphite interlayer spacing, increasing the graphite interlayer spacing, which is beneficial for iron to enter the interior of the nitrogen-carbon substrate during subsequent chemical vapor deposition and replace tin, which helps to improve the acidic oxygen reduction activity. The graphite intercalation ability of the tin-based precursor increases the graphite degree of carbon in the nitrogen-carbon substrate, reduces defective carbon, and improves the stability of the Fe-Sn-NC cathode oxygen reduction catalyst. When used in proton exchange membrane fuel cells, since iron and tin are fixed inside the nitrogen-carbon substrate, the dissolution of iron and tin active sites is reduced, and the cycle stability of the Fe-Sn-NC cathode oxygen reduction catalyst is improved.
[0017] The preparation method of the invention is simple, easy to implement, environmentally friendly and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A flow chart showing a method for preparing a Fe-Sn-NC cathode oxygen reduction catalyst according to an embodiment of the present invention;
[0019] Figure 2a The scanning electron microscope image of the nitrogen-carbon substrate (NC) prepared in Example 1 of the present invention is shown;
[0020] Figure 2b shows a scanning electron microscope image of the Sn-NC composite solid (SnNC) prepared in Example 1 of the present invention;
[0021] Figure 2c The scanning electron microscope image of the Fe-Sn-NC cathode oxygen reduction catalyst 1 (SnFeNC) prepared in Example 1 of the present invention is shown;
[0022] Figure 3The half-wave potential curve of the Fe-Sn-NC cathode oxygen reduction catalyst 1 prepared in Example 1 of the present invention in a 0.1M perchloric acid solution is shown;
[0023] Figure 4 The graphs show the half-wave potential curves of the Fe-Sn-NC cathode oxygen reduction catalyst 1 prepared in Example 1 of the present invention in a 0.1M perchloric acid solution in the initial state, before and after 10,000 cycles, 20,000 cycles, 30,000 cycles, 50,000 cycles and 70,000 cycles of accelerated aging test;
[0024] Figure 5 A curve diagram showing the power density and voltage of the Fe-Sn-NC cathode oxygen reduction catalyst 1 prepared in Example 1 of the present invention as a function of current;
[0025] Figure 6 The Raman shifts of the nitrogen-carbon substrate, Sn-NC composite solid, and Fe-Sn-NC cathode oxygen reduction catalyst 1 prepared in Example 1 of the present invention are shown;
[0026] Figure 7 The in-situ Raman scattering patterns (SERS) of the Sn-NC composite solid prepared in Example 1 of the present invention, the Fe-Sn-NC cathode oxygen reduction catalyst 1, and the Fe-NC cathode oxygen reduction catalyst 1' (FeNC) prepared in Comparative Example 1 are shown, wherein a is an in-situ Raman scattering pattern of FeNC; b is a columnar change pattern of the graphitization degree of FeNC; c is an in-situ Raman scattering pattern of SnNC; d is a columnar change pattern of the graphitization degree of SnNC; e is an in-situ Raman scattering pattern of SnFeNC; and f is a columnar change pattern of the graphitization degree of SnFeNC;
[0027] Figure 8 X-ray diffraction spectra of the nitrogen-carbon substrate, Sn-NC composite solid, Fe-Sn-NC cathode oxygen reduction catalyst 1 prepared in Example 1 of the present invention, and Fe-NC cathode oxygen reduction catalyst 1' prepared in Comparative Example 1 are shown. DETAILED DESCRIPTION
[0028] Below, embodiments of the present invention will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of embodiments of the present invention. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of concepts of the present invention.
[0029] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. The term "comprising" used herein indicates the existence of features, steps, operations, but does not exclude the existence or addition of one or more other features.
[0030] In the case of using expressions such as "at least one of A, B, and C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, and C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.). In the case of using expressions such as "at least one of A, B, or C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, or C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.).
[0031] In response to the phenomenon of single-atom site dissolution of non-precious metal single-atom catalysts in acidic oxygen reduction environments, related technologies mostly use methods such as introducing free radical scavengers to inhibit single-atom dissolution, designing a more stable local coordination structure of MNC catalysts, or increasing the density of single-atom active sites.
[0032] One approach in the related art is to introduce Ce 3+ / 4+ Redox couples act as free radical scavengers to protect single atom catalysts from free radical attacks, but since such free radical scavengers have no oxygen reduction activity, they have little effect on improving the initial power density of the battery.
[0033] Another approach in related technologies is to optimize the active site structure by constructing multi-center structures, introducing heteroatom groups, and locally modulating the MN coordination structure. However, it is difficult to effectively take into account the active site density, and the effect on improving the volume-to-power ratio is minimal.
[0034] In the process of realizing the concept of the present invention, it was found that the Fe-NC single-atom catalyst has good oxygen reduction activity under acidic conditions and can catalyze oxygen reduction well. However, when applied to proton exchange membrane fuel cells, due to the Fenton reaction under acidic conditions, the iron active sites are dissolved in the form of particles under operating conditions, which further reduces the catalytic ability and stability of the Fe-NC single-atom catalyst.
[0035] Furthermore, in order to solve the above problems, the present invention utilizes the good graphite intercalation ability of the tin-based precursor to insert tin into the interior of the nitrogen-carbon substrate, and then fixes the tin through calcination to form a Sn-N4 active site with the surrounding nitrogen, and then chemical vapor deposition is carried out with the iron-based precursor to allow the iron to replace part of the tin to form a Fe-Sn bimetallic single atom site. Based on the graphite intercalation ability of the tin-based precursor, the loading on the obtained single atom site is relatively high.
[0036] Specifically, according to an embodiment of one aspect of the present invention, a method for preparing a Fe-Sn-NC cathode oxygen reduction catalyst is provided. Figure 1 A flow chart of a method for preparing a Fe-Sn-NC cathode oxygen reduction catalyst according to an embodiment of the present invention is shown. Figure 1 As shown, the preparation method includes operations S101 to S104.
[0037] In operation S101 , ZIF-8 having a regular dodecahedron framework structure is pyrolyzed under a protective atmosphere to obtain a carbonized nitrogen-carbon substrate, wherein the nitrogen-carbon substrate has a regular dodecahedron framework structure.
[0038] According to an embodiment of the present invention, ZIF-8 having a regular dodecahedral framework structure is used as a carrier, which can maintain a high specific surface area and a relatively rich pore structure after pyrolysis, which helps to increase the number of active sites for subsequent catalyst formation, thereby improving the catalytic effect. The protective atmosphere can be, for example, at least one of nitrogen and argon. At a higher pyrolysis temperature (for example, 900 to 1000° C.), at high temperature, the organic ligands in ZIF-8 decompose into carbon, leaving a skeleton of a regular dodecahedral framework structure.
[0039] In operation S102 , a tin-based precursor is mixed with a carbon nitride substrate and heated to obtain a tin-intercalated carbon nitride substrate.
[0040] According to an embodiment of the present invention, the tin-based precursor can be understood as a tin salt compound containing tin ions. With the help of the unique graphite intercalation ability of the tin-based precursor, the tin salt precursor can penetrate into the interior of the nitrogen-carbon substrate. The embedding of tin helps to expand the graphite interlayer spacing of the nitrogen-carbon substrate, providing a larger space for the subsequent deposition of iron, making it easier for iron to enter the interior of the nitrogen-carbon substrate, which helps to increase the number and density of active sites formed.
[0041] In operation S103, the Sn-intercalated carbonitride substrate is calcined to obtain a Sn-NC composite solid.
[0042] According to an embodiment of the present invention, calcination helps to fix tin inside the nitrogen-carbon substrate, so that tin and nitrogen form a bond to form a Sn-N4 active center.
[0043] In operation S104, the Sn-NC composite solid and the iron-based precursor are chemically vapor deposited to obtain a Fe-Sn-NC cathode oxygen reduction catalyst.
[0044] According to an embodiment of the present invention, iron is uniformly dispersed on the surface and inside of the nitrogen-carbon substrate by chemical vapor deposition, so that iron partially replaces tin and is fixed in Fe-N4 and Sn-N4 inside the nitrogen-carbon substrate, wherein Fe and Sn are coordinated and bonded to form Fe-Sn bimetallic single atom sites, so that the single atom loading in the nitrogen-carbon substrate is higher, and it has a higher half-wave potential and better cycle stability in the acidic oxygen reduction reaction.
[0045] According to an embodiment of the present invention, the graphite interlayer spacing of the nitrogen-carbon substrate is modified by the intervention of a tin-based precursor, and when an iron-based precursor is subsequently used for replacement, it is beneficial for iron to enter the interior of the nitrogen-carbon substrate, thereby increasing the density of active sites and thus improving the catalytic activity and stability of the Fe-Sn-NC cathode oxygen reduction catalyst. In addition, due to the insertion of the tin-based precursor, the degree of graphitization of the nitrogen-carbon substrate is improved. When it is subsequently applied to the oxygen reduction process in an acidic environment, the iron undergoes less Fenton reaction, and the decomposition of the nitrogen-carbon substrate is reduced, resulting in less dissolution of active sites of iron and tin, further improving the catalytic activity and cycle stability of the Fe-Sn-NC cathode oxygen reduction catalyst.
[0046] According to an embodiment of the present invention, ZIF-8 is prepared by the following process: zinc nitrate or its hydrate and dimethylimidazole are dispersed in a methanol solution and mixed to obtain a mixed solution; the mixed solution is centrifuged and dried in sequence to obtain ZIF-8.
[0047] In one embodiment, zinc nitrate or its hydrate is dissolved in a methanol solution to obtain a zinc nitrate solution. Dimethylimidazole is dissolved in a methanol solution to obtain a dimethylimidazole solution. The zinc nitrate solution is added to the dimethylimidazole solution, stirred and mixed to obtain a mixed solution. Zinc nitrate or its hydrate and dimethylimidazole have high solubility in methanol, and zinc ions and dimethylimidazole molecules are formed during the dissolution process. During the mixing process, the two interact through electrostatic attraction to form a complex. As needed, it can be left to stand for a period of time after mixing to promote the complex to assemble into the crystal structure of ZIF-8, and then the unreacted raw materials and by-products are removed by centrifugation, and the residual solvent is removed by drying.
[0048] According to an embodiment of the present invention, the mass ratio of zinc nitrate to dimethylimidazole is (2-4): (5.5-7.5), preferably 3: 6.5. For example, 3 g of zinc nitrate hexahydrate can be dissolved in 40 mL of methanol solution to form a zinc nitrate solution, and 6.5 g of dimethylimidazole can be dissolved in 80 mL of methanol solution to form a dimethylimidazole solution.
[0049] Preferably, the mixing time of the mixture is 24 hours, the speed of centrifugation is 10000 rpm, the centrifugation time is 3 minutes, and the mixture can be washed with methanol as needed after centrifugation, for example, 3 times. The drying method can be vacuum drying, the drying temperature is 55-60°C, preferably 60°C, and the drying time is 12 hours.
[0050] In one embodiment, the pyrolysis conditions in operation S101 may be, for example, calcination at 950° C. for 1 hour, and the atmosphere used may be, for example, argon gas, and the flow rate of argon gas may be 40 sccm. Most of the zinc ions in the nitrogen-carbon substrate are evaporated by calcination to form a graphitized structure of the nitrogen-carbon substrate.
[0051] According to an embodiment of the present invention, ZIF-8 having a regular dodecahedral framework structure is used as a carrier, which can maintain a high specific surface area and a relatively rich pore structure after pyrolysis, which helps to increase the number of active sites for subsequent catalyst formation, thereby improving the catalytic effect.
[0052] According to an embodiment of the present invention, operation S102 includes sub-operations S1021-S1022.
[0053] In sub-operation S1021, the tin-based precursor and the nitrogen-carbon substrate are ground at room temperature for 10 to 20 minutes to obtain a mixture.
[0054] In sub-operation S1022, the mixture is heated from room temperature to (300-400)°C, for example, 300°C, 350°C or 400°C, preferably 300°C. The temperature is maintained at (300-400)°C for 1-3 hours, with a heating rate of (4-6)°C / min, preferably 5°C / min.
[0055] According to an embodiment of the present invention, grinding is performed to fully and evenly mix the tin-based precursor and the nitrogen-carbon substrate, which helps the two to interact after subsequent heating. By heating, the tin ions replace part of the zinc ions retained in the nitrogen-carbon substrate. Continuing to maintain the temperature at (300~400)°C for a certain period of time helps the tin ions to interact with nitrogen, forming Sn-N4 active sites, thereby fixing the tin inside the nitrogen-carbon substrate.
[0056] Preferably, the grinding time is 15 min.
[0057] More preferably, the molar ratio of the tin-based precursor to the nitrogen-carbon substrate is 1: (1-7.5), for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:5.5, 1:6, 1:6.5, 1:7 or 1:7.5, preferably 1:5. If too much tin-based precursor is added, tin particles are easily formed; if too little tin-based precursor is added, the single-atom loading of tin ions at the active site is insufficient, and the catalytic activity is poor. The tin salt precursor includes at least one of tin tetrachloride, tin tetrachloride hydrate, and stannous chloride, preferably tin tetrachloride or tin tetrachloride hydrate. The boiling points of the above-mentioned tin salt precursors are all lower than 700°C, which is lower than the boiling point of the iron-based precursor, which helps to be partially replaced by iron ions during the subsequent chemical vapor deposition process. When the tin-based precursor uses tin tetrachloride or tin tetrachloride hydrate, it can be more easily fixed in the nitrogen-carbon substrate due to its low boiling point.
[0058] According to an embodiment of the present invention, operation S103 specifically includes: in a protective atmosphere, heating the tin-inserted nitrogen-carbon substrate from (300-400)°C to 750°C at a heating rate of (4-6)°C / min, preferably, the heating rate is 5°C / min, and calcining at 750°C for 1.5-2.5h, preferably calcining for 2h, heating to 900°C at a heating rate of (4-6)°C / min, preferably, the heating rate is 5°C / min, and continuing to calcine at 900°C for 0.5-1.5h, preferably calcining for 1h, to obtain a Sn-NC composite solid. Calcination at 750°C helps to remove volatile components present therein, and the second calcination at 900°C helps to promote the rearrangement of atoms inside the tin-inserted nitrogen-carbon substrate, so that the obtained Sn-NC composite solid has better compactness and more stable structure.
[0059] According to an embodiment of the present invention, operation S104 includes sub-operations S1041 - S1042 .
[0060] In sub-operation S1041, the Sn-NC composite solid and the iron-based precursor are chemically vapor deposited at 700-800° C. under inert gas conditions for 2-4 hours to obtain a Fe-Sn-NC cathode oxygen reduction catalyst precursor.
[0061] In sub-operation S1042, the Fe-Sn-NC cathode oxygen reduction catalyst precursor is acid-washed and dried to obtain the Fe-Sn-NC cathode oxygen reduction catalyst.
[0062] According to an embodiment of the present invention, the iron-based precursor can form a gas state at the above high temperature (700-800°C), enter the Sn-NC composite solid, replace the remaining zinc ions and part of the tin ions, so that the iron ions and nitrogen form Fe-N4 active sites, and the iron ions and tin ions are coordinated to form bonds, thereby reducing the dissolution of iron ions and tin ions in subsequent applications in an acidic oxygen reduction environment, and improving the single atom loading and cycle stability of the Fe-Sn-NC cathode oxygen reduction catalyst. Pickling helps to remove impurities such as iron-based precursor particles on the surface of the Fe-Sn-NC cathode oxygen reduction catalyst precursor. Drying treatment helps to remove moisture and other volatile substances on the surface of the Fe-Sn-NC cathode oxygen reduction catalyst precursor, so that the purity of the prepared Fe-Sn-NC cathode oxygen reduction catalyst is improved.
[0063] For example, the process of chemical vapor deposition can be understood as follows: an iron-based precursor is placed in the lower part of a container, and a Sn-NC composite solid is placed in the upper part of the container, and the upper and lower parts of the container are separated by a gas phase membrane, and the container used can be, for example, a porcelain boat. Then, pyrolysis is performed to form a gaseous state of the iron-based precursor, which is then deposited on the surface and inside of the Sn-NC composite solid after passing through the gas phase membrane.
[0064] Furthermore, the iron-based precursor includes at least one of ferrous chloride, ferrous chloride hydrate, and ferric chloride. Ferrous chloride is easily decomposed at high temperatures (700-800°C), while the boiling point of ferric chloride is around 300°C. During the vapor deposition process, iron ions can easily enter the interior of the Sn-NC composite solid. The molar ratio of the Sn-NC composite solid to the iron-based precursor is (1-1.5):1, for example, it can be 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1, preferably 1:1. If too much iron-based precursor is added, iron particles are easily formed; if too little iron-based precursor is added, the single-atom loading of iron ions at the active site is insufficient, and the catalytic activity is poor.
[0065] Preferably, the pH of the pickling is 0.5-1.5, and more preferably, the pH of the pickling is 1. The acidic solution used for pickling can be, for example, a 0.5-1 mol / L sulfuric acid solution, and the pickling can be done overnight to remove impurities such as iron-based precursor particles more thoroughly. The drying temperature is 60° C., and the drying method is vacuum drying. The drying can be done overnight to remove moisture and other volatile substances more fully.
[0066] In a specific embodiment, the preparation process of the Fe-Sn-NC cathode oxygen reduction catalyst is as follows:
[0067] Zinc nitrate hexahydrate is dissolved in a methanol solution to obtain a zinc nitrate solution.
[0068] Dissolve dimethylimidazole in methanol solution to obtain a dimethylimidazole solution.
[0069] The zinc nitrate solution is added to the dimethylimidazole solution, and the mixture is stirred to obtain a mixed solution.
[0070] The mixed solution was centrifuged, washed with methanol and vacuum dried in sequence to obtain ZIF-8.
[0071] Under a protective gas atmosphere, ZIF-8 was pyrolyzed to obtain a carbonized nitrogen-carbon substrate.
[0072] The tin-based precursor is mixed with the nitrogen-carbon substrate and heated to obtain the tin-intercalated nitrogen-carbon substrate.
[0073] The Sn-intercalated carbonitride substrate is calcined to obtain a Sn-NC composite solid.
[0074] The Sn-NC composite solid and the iron-based precursor are chemically vapor deposited, and then acid-washed, filtered and dried in sequence to obtain a Fe-Sn-NC cathode oxygen reduction catalyst.
[0075] According to an embodiment of another aspect of the present invention, there is provided an Fe-Sn-NC cathode oxygen reduction catalyst prepared by the preparation method as described above, comprising: a nitrogen-carbon substrate having a regular dodecahedral framework structure; and an active center comprising a Fe-Sn bimetallic single atom site loaded inside the nitrogen-carbon substrate; wherein iron and tin are coordinated to form a bond.
[0076] According to an embodiment of the present invention, the active center of iron is Fe-N4, the active center of tin is Sn-N4, and the iron and tin are coordinated to form a bond, forming a Fe-Sn bimetallic single atom site supported on the surface and inside of the nitrogen-carbon substrate. The present invention is based on an intercalated graphite layer, and the single atom loading of the obtained Fe-Sn-NC cathode oxygen reduction catalyst is high, and it has a high half-wave potential and cycle stability when applied to acidic oxygen reduction reactions. By forming a Fe-Sn bimetallic single atom site, the dissolution of iron and tin in the form of particles caused by the Fenton phenomenon in the application of fuel cell cathodes is suppressed, and the single atom stability of iron and tin is further improved.
[0077] Furthermore, the mass fraction of iron in the Fe-Sn-NC cathode oxygen reduction catalyst is 1-2%, for example, 1%, 1.5% or 2%. This indicates that by fixing the above content of iron on the nitrogen-carbon substrate, the electronic structure of the Fe-N4 active center can be optimized, and the catalytic efficiency of the Fe-Sn bimetallic single atom site can be improved.
[0078] According to another embodiment of the present invention, there is provided an application of the Fe—Sn—NC cathode oxygen reduction catalyst as described above in the field of cathode technology of proton exchange membrane fuel cells.
[0079] According to an embodiment of the present invention, the iron and tin in the catalyst are dispersed in single atoms, which can form more active sites, so that the catalytic activity of the Fe-Sn-NC cathode oxygen reduction catalyst per unit mass is higher, and the Fe-SNC cathode oxygen reduction catalyst has a higher half-wave potential, which can effectively catalyze the oxygen reduction reaction at a lower potential. Due to the coordination between iron and tin, and the graphitization of the nitrogen-carbon substrate, the occurrence of the Fenton reaction is reduced, thereby reducing the dissolution of metals on the active sites under working conditions, improving the cycle stability of the catalyst, and then improving the voltage output and energy efficiency of the fuel cell, and having both high catalytic activity and stability, significantly improving the performance of the fuel cell, and extending the service life of the battery.
[0080] In one of the embodiments, the half-wave potential of the Fe-Sn-NC cathode oxygen reduction catalyst can reach 0.85V, which has a wide range of applicability in the field of proton exchange membrane fuel cell technology.
[0081] The present invention is further described below by embodiments and related test experiments and results thereof. In the detailed description below, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present invention. However, it is obvious that one or more embodiments may also be implemented without these specific details. And, in the absence of conflict, the details in the following embodiments may be combined into other feasible embodiments at will.
[0082] It should be noted that the following specific examples are only for illustration, and the protection scope of the present invention is not limited thereto. The chemicals and raw materials used in the following examples are all commercially available or homemade by recognized processing methods.
[0083] Embodiment 1:
[0084] Add 3.0 g of zinc nitrate hexahydrate to 40 mL of methanol at room temperature and stir until completely dissolved to obtain a zinc nitrate solution. Add 6.5 g of dimethylimidazole to 80 mL of methanol and stir until completely dissolved to obtain a dimethylimidazole solution. Under stirring, slowly add 40 mL of zinc nitrate methanol solution to 80 mL of dimethylimidazole methanol solution, and then stir at room temperature for 24 hours to obtain a first suspension. Centrifuge the first suspension at 10,000 rpm for 3 minutes, wash it 3 times with a methanol solution, and then dry it in a vacuum drying oven at 60°C for 12 hours to obtain ZIF-8.
[0085] ZIF-8 was placed in a tube furnace and calcined at 950 °C for 1 h under an argon atmosphere to obtain a nitrogen-carbon substrate after pyrolysis and carbonization.
[0086] Figure 2a FIG. 4 shows a scanning electron microscope image of the nitrogen-carbon substrate (NC) prepared in Example 1 of the present invention. Figure 2a As shown, it can be seen that the nitrogen-carbon substrate prepared in Example 1 has a regular dodecahedral structure.
[0087] The nitrogen-carbon substrate and tin tetrachloride pentahydrate were ground for 15 minutes at a mass ratio of 1 to obtain a mixture. The temperature was raised from room temperature to 300°C at a heating rate of 5°C / min, and maintained at 300°C for 2 hours to obtain a tin-intercalated nitrogen-carbon substrate. It was placed in a tubular furnace, heated from 300°C to 750°C at a heating rate of 5°C / min under pure nitrogen conditions, and calcined at 750°C for 2 hours, and then heated to 900°C at a heating rate of 5°C / min, and continued to calcine for 1 hour to obtain a Sn-NC composite solid.
[0088] Figure 2b FIG. 4 shows a scanning electron microscope image of the Sn-NC composite solid (SnNC) prepared in Example 1 of the present invention. Figure 2b As shown, it can be seen that the Sn-NC composite solid still maintains a good regular dodecahedron structure.
[0089] The Sn-NC composite solid and ferrous chloride tetrahydrate were chemically vapor deposited at a molar ratio of 1 under pure nitrogen conditions at 750°C for 3 hours to obtain a Fe-Sn-NC cathode oxygen reduction catalyst precursor, which was then acid washed with 60 mL of 0.5 M sulfuric acid for 8 hours, and then filtered and the filter cake was washed with 4 L of ultrapure water. The filter cake was placed in a vacuum drying oven and dried for 12 hours. Finally, it was ground to obtain a Fe-Sn-NC cathode oxygen reduction catalyst 1 with high oxygen reduction activity and stability.
[0090] Figure 2c FIG. 1 shows a scanning electron microscope image of the Fe-Sn-NC cathode oxygen reduction catalyst 1 (SnFeNC) prepared in Example 1 of the present invention. Figure 2c As shown, it can be seen that the structure of SnFeNC is still well maintained.
[0091] The performance of the Fe-Sn-NC cathode oxygen reduction catalyst 1 of Example 1 was tested:
[0092] Test the three-electrode oxygen reduction activity: Figure 3 The half-wave potential curve of the Fe-Sn-NC cathode oxygen reduction catalyst 1 prepared in Example 1 of the present invention in a 0.1M perchloric acid solution is shown. Figure 3As shown, the Fe-Sn-NC cathode oxygen reduction catalyst 1 exhibited a high oxygen reduction activity of 0.85V.
[0093] Conduct three-electrode stability test: Figure 4 The half-wave potential curves of the Fe-Sn-NC cathode oxygen reduction catalyst 1 prepared in Example 1 of the present invention in 0.1M perchloric acid solution are shown in the initial state, before and after 10,000 cycles, 20,000 cycles, 30,000 cycles, 50,000 cycles and 70,000 cycles of accelerated aging test. Figure 4 As shown, under saturated oxygen conditions, the voltage range is 0.6-0.9V (vs RHE), the 7W cycle half-wave loss is 28mV, and the Fe-Sn-NC cathode oxygen reduction catalyst 1 exhibits relatively excellent acidic oxygen reduction stability.
[0094] Conducting tests on membrane electrode assemblies: Figure 5 The power density and voltage of the Fe-Sn-NC cathode oxygen reduction catalyst 1 prepared in Example 1 of the present invention are shown as a curve of the change of current. Figure 5 As shown in the figure, it can be clearly seen that the membrane electrode assembled with Fe-Sn-NC catalyst has a nearly 1.8W / cm 2 Excellent performance.
[0095] Figure 6 The Raman shifts of the nitrogen-carbon substrate (NC), Sn-NC composite solid (SnNC), and Fe-Sn-NC cathode oxygen reduction catalyst 1 (SnFeNC) prepared in Example 1 of the present invention are shown. Figure 6 As shown, the poured A D / A G It represents the peak area ratio of the carbon peaks of the three materials. The specific values are shown in Table 1. It can be seen that the ratio of SnFeNC is lower. The reason is that the degree of graphitization of the nitrogen-carbon substrate is higher, which reduces the carbon defects of the carbon layer.
[0096] Table 1 Comparison of carbon peak area ratios of three materials
[0097]
[0098] The nitrogen-carbon substrate (NC), Sn-NC composite solid (SnNC), and Fe-Sn-NC cathode oxygen reduction catalyst 1 (SnFeNC) prepared in Example 1 of the present invention were respectively subjected to inductively coupled plasma (ICP) tests, and the obtained data are shown in Table 2. It can be seen that the fixation of Sn replaces part of Zn, and after subsequent chemical vapor deposition, Fe replaces part of Sn and Zn, and still has a half-wave potential of 0.85 V when the single atom loading of Fe is 1.37 wt%.
[0099] Table 2 Comparison of single atom loadings on active sites of three materials
[0100]
[0101] Comparative Example 1:
[0102] The preparation process of this comparative example 1 is substantially the same as that of the example 1, except that after obtaining the carbonized nitrogen-carbon substrate, it is directly subjected to chemical vapor deposition with ferrous chloride tetrahydrate to obtain the Fe-NC cathode oxygen reduction catalyst (FeNC).
[0103] Figure 7 The in-situ Raman scattering patterns (SERS) of the Sn-NC composite solid prepared in Example 1 of the present invention, the Fe-Sn-NC cathode oxygen reduction catalyst 1, and the Fe-NC cathode oxygen reduction catalyst 1' (FeNC) prepared in Comparative Example 1 are shown, wherein a is the in-situ Raman scattering pattern of FeNC; b is the columnar change pattern of the graphitization degree of FeNC; c is the in-situ Raman scattering pattern of SnNC; d is the columnar change pattern of the graphitization degree of SnNC; e is the in-situ Raman scattering pattern of SnFeNC; and f is the columnar change pattern of the graphitization degree of SnFeNC. Figure 7 As shown in a in the figure, the green box represents the change of Fenton free radicals, and the corresponding D peak intensity / G peak intensity represents the degree of graphitization of carbon (the smaller the number, the fewer defects, the better the stability, and the smaller the increase, the better). Figure 7 As shown in a~f in the figure, during the constant voltage polarization test, it can be seen that the degree of graphitization of SnFeNC is higher, resulting in less Fenton reaction, less decomposition of the nitrogen-carbon substrate, and less dissolution of the iron and tin active sites.
[0104] Figure 8 The X-ray diffraction spectra of the nitrogen-carbon substrate, Sn-NC composite solid, Fe-Sn-NC cathode oxygen reduction catalyst 1 prepared in Example 1 of the present invention and Fe-NC cathode oxygen reduction catalyst 1' prepared in Comparative Example 1 are shown. Figure 8 As shown, the carbon (002) peak corresponding to about 26° can be found to have an obvious shift to a lower angle in SnNC, indicating that tin ions with a larger radius are inserted into the graphite layer, resulting in a larger interlayer spacing and a shift of the diffraction angle to a lower angle. This state of larger interlayer spacing and shifted diffraction angle is still maintained in the formed Fe-Sn-NC cathode oxygen reduction catalyst 1, verifying the modification of the graphite interlayer spacing by the intercalation of tin tetrachloride pentahydrate.
[0105] Embodiment 2:
[0106] The preparation process of this embodiment 2 is substantially the same as that of embodiment 1, except that the nitrogen-carbon substrate and tin tetrachloride pentahydrate are ground in a molar ratio of 1:5.5 to prepare the Fe-Sn-NC cathode oxygen reduction catalyst 2.
[0107] The Fe—Sn—NC cathode oxygen reduction catalyst 2 prepared in Example 2 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe—Sn—NC cathode oxygen reduction catalyst 2 was found to be 0.846V.
[0108] Embodiment 3:
[0109] The preparation process of this embodiment 3 is substantially the same as that of embodiment 1, except that the nitrogen-carbon substrate and tin tetrachloride pentahydrate are ground in a molar ratio of 1:6 to prepare the Fe-Sn-NC cathode oxygen reduction catalyst 3.
[0110] The Fe—Sn—NC cathode oxygen reduction catalyst 3 prepared in Example 3 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe—Sn—NC cathode oxygen reduction catalyst 3 was found to be 0.844V.
[0111] Embodiment 4:
[0112] The preparation process of this embodiment 4 is substantially the same as that of embodiment 1, except that the nitrogen-carbon substrate and tin tetrachloride pentahydrate are ground in a molar ratio of 1:6.5 to prepare Fe-Sn-NC cathode oxygen reduction catalyst 4.
[0113] The Fe—Sn—NC cathode oxygen reduction catalyst 4 prepared in this Example 4 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe—Sn—NC cathode oxygen reduction catalyst 4 was found to be 0.843V.
[0114] Embodiment 5:
[0115] The preparation process of this embodiment 5 is substantially the same as that of embodiment 1, except that the nitrogen-carbon substrate and tin tetrachloride pentahydrate are ground in a molar ratio of 1:7.5 to prepare Fe-Sn-NC cathode oxygen reduction catalyst 5.
[0116] The Fe—Sn—NC cathode oxygen reduction catalyst 5 prepared in this Example 5 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe—Sn—NC cathode oxygen reduction catalyst 5 was found to be 0.84V.
[0117] Embodiment 6:
[0118] The preparation process of this embodiment 6 is substantially the same as that of embodiment 1, except that the Sn-NC composite solid and ferrous chloride tetrahydrate are chemically vapor deposited at a molar ratio of 1:1 to prepare the Fe-Sn-NC cathode oxygen reduction catalyst 6.
[0119] The Fe—Sn—NC cathode oxygen reduction catalyst 6 prepared in Example 6 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe—Sn—NC cathode oxygen reduction catalyst 6 was found to be 0.85V.
[0120] Embodiment 7:
[0121] The preparation process of this embodiment 7 is substantially the same as that of embodiment 1, except that the Sn-NC composite solid and ferrous chloride tetrahydrate are chemically vapor deposited at a molar ratio of 1:1.2 to prepare the Fe-Sn-NC cathode oxygen reduction catalyst 7.
[0122] The Fe—Sn—NC cathode oxygen reduction catalyst 7 prepared in this Example 7 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe—Sn—NC cathode oxygen reduction catalyst 7 was found to be 0.852V.
[0123] Embodiment 8:
[0124] The preparation process of this embodiment 8 is substantially the same as that of embodiment 1, except that the Sn-NC composite solid and ferrous chloride tetrahydrate are chemically vapor deposited at a molar ratio of 1:1.3 to prepare the Fe-Sn-NC cathode oxygen reduction catalyst 8.
[0125] The Fe—Sn—NC cathode oxygen reduction catalyst 8 prepared in Example 8 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe—Sn—NC cathode oxygen reduction catalyst 8 was found to be 0.853V.
[0126] Embodiment 9:
[0127] The preparation process of this embodiment 9 is substantially the same as that of embodiment 1, except that the Sn-NC composite solid and ferrous chloride tetrahydrate are chemically vapor deposited at a molar ratio of 1:1.4 to prepare the Fe-Sn-NC cathode oxygen reduction catalyst 9.
[0128] The Fe—Sn—NC cathode oxygen reduction catalyst 9 prepared in Example 9 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe—Sn—NC cathode oxygen reduction catalyst 9 was found to be 0.854V.
[0129] Embodiment 10:
[0130] The preparation process of this embodiment 10 is substantially the same as that of embodiment 1, except that the Sn-NC composite solid and ferrous chloride tetrahydrate are chemically vapor deposited at a molar ratio of 1:1.5 to prepare the Fe-Sn-NC cathode oxygen reduction catalyst 10.
[0131] The Fe—Sn—NC cathode oxygen reduction catalyst 10 prepared in this embodiment 10 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe—Sn—NC cathode oxygen reduction catalyst 10 was found to be 0.856V.
[0132] Embodiment 11:
[0133] The preparation process of this embodiment 11 is substantially the same as that of embodiment 1, except that the tin-intercalated nitrogen-carbon substrate is heated to 750° C. and calcined for 3 h to prepare the Fe—Sn—NC cathode oxygen reduction catalyst 11.
[0134] The Fe—Sn—NC cathode oxygen reduction catalyst 11 prepared in this Example 11 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe—Sn—NC cathode oxygen reduction catalyst 11 was found to be 0.852V.
[0135] Embodiment 12:
[0136] The preparation process of this embodiment 12 is generally the same as that of embodiment 1, except that the nitrogen-carbon substrate and tin tetrachloride pentahydrate are ground in a molar ratio of 1:7.5, and the Sn-NC composite solid and ferrous chloride tetrahydrate are chemically vapor deposited in a molar ratio of 1:1.5 to prepare the Fe-Sn-NC cathode oxygen reduction catalyst 12.
[0137] The Fe—Sn—NC cathode oxygen reduction catalyst 12 prepared in this Example 12 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe—Sn—NC cathode oxygen reduction catalyst 12 was found to be 0.854V.
[0138] It can be seen from the preparation results of Examples 1 to 12 of the present invention that the Fe-Sn-NC cathode oxygen reduction catalyst prepared by the above steps can have a high oxygen reduction catalytic activity while maintaining a high cycle stability, and can be applied to proton exchange membrane fuel cells.
[0139] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a Fe-Sn-NC cathode oxygen reduction catalyst, comprising: Under a protective atmosphere, pyrolyzing ZIF-8 having a regular dodecahedron framework structure to obtain a carbonized nitrogen-carbon substrate, wherein the nitrogen-carbon substrate has a regular dodecahedron framework structure; Mixing a tin-based precursor with the nitrogen-carbon substrate and heating them to obtain a tin-intercalated nitrogen-carbon substrate; calcining the tin-intercalated nitrogen-carbon substrate to obtain a Sn-NC composite solid; The Sn-NC composite solid is chemically vapor deposited with an iron-based precursor to obtain a Fe-Sn-NC cathode oxygen reduction catalyst.
2. The preparation method according to claim 1, wherein The Sn-NC composite solid and the iron-based precursor are subjected to chemical vapor deposition to obtain the Fe-Sn-NC cathode oxygen reduction catalyst, which comprises: The Sn-NC composite solid and the iron-based precursor were chemically vapor deposited at 700-800°C under inert gas conditions for 2-4 hours to obtain the Fe-Sn-NC cathode oxygen reduction catalyst precursor; The Fe—Sn—NC cathode oxygen reduction catalyst precursor is subjected to acid washing and drying treatment to obtain the Fe—Sn—NC cathode oxygen reduction catalyst.
3. The preparation method according to claim 1, wherein The step of mixing the tin-based precursor with the nitrogen-carbon substrate and heating the mixture comprises: Grinding the tin-based precursor and the nitrogen-carbon substrate at room temperature for 10 to 20 minutes to obtain a mixture; The mixture is heated from room temperature to (300-400)°C, maintained at (300-400)°C for 1-3 hours, and the heating rate is (4-6)°C / min.
4. The preparation method according to claim 3, wherein The molar ratio of the tin-based precursor to the nitrogen-carbon substrate is 1:(1-7.5), and the tin salt precursor includes at least one of tin tetrachloride, tin tetrachloride hydrate, and stannous chloride.
5. The preparation method according to claim 1, wherein The calcining of the tin-intercalated nitrogen-carbon substrate to obtain a Sn-NC composite solid comprises: Under a protective atmosphere, the Sn-inserted nitrogen-carbon substrate is heated from (300-400)°C to 750°C at a heating rate of (4-6)°C / min, and calcined at 750°C for 1.5-2.5h, then heated to 900°C at a heating rate of (4-6)°C / min, and further calcined at 900°C for 0.5-1.5h to obtain the Sn-NC composite solid.
6. The preparation method according to claim 1, wherein The iron-based precursor includes at least one of ferrous chloride, ferrous chloride hydrate, and ferric chloride; The molar ratio of the Sn-NC composite solid to the iron-based precursor is (1-1.5):
1.
7. The preparation method according to claim 2, wherein: The pH of the pickling is 0.5-1.5, and the drying temperature is 60°C.
8. The preparation method according to claim 1, wherein ZIF-8 was prepared by the following process: Dispersing zinc nitrate or its hydrate and dimethylimidazole in a methanol solution respectively and mixing them to obtain a mixed solution; The mixed solution is centrifuged and dried in sequence to obtain ZIF-8; The mass ratio of zinc nitrate or its hydrate and dimethylimidazole is (2~4):(5.5~7.5).
9. A Fe-Sn-NC cathode oxygen reduction catalyst prepared by the preparation method according to claims 1 to 8, comprising: The nitrogen-carbon substrate has a regular dodecahedral framework structure; as well as Active centers, including Fe-Sn bimetallic single atom sites supported inside the nitrogen-carbon substrate; Among them, iron and tin are coordinated to form a bond, and the mass fraction of iron in the Fe-Sn-NC cathode oxygen reduction catalyst is 1-2%.
10. Use of the Fe-Sn-NC cathode oxygen reduction catalyst as claimed in claim 9 in the field of proton exchange membrane fuel cell cathode technology.
Citation Information
Patent Citations
Preparation method and application of FeSn compound coated NC electrocatalyst
CN114464821A
Preparation method and application of MnO / Sn-NC electrocatalyst
CN116190680A
Sn-doped Fe-N-C catalyst as well as preparation method and application thereof
CN116344851A
Preparation method and application of bimetallic monatomic catalyst derived from MOF precursor
CN118360627A
Preparation method and application of iron-based heteronuclear diatomic active site oxygen reduction catalyst
CN119050385A
Cited By
Fe-Sn diatomic site catalyst and preparation method thereof
CN121172161A